Pengaruh Kepemimpinan, Iklim Organisasi, dan Motivasi Kerja Terhadap Kinerja PT. Perkebunan Nusantara VII (PTPN VII) Betung - Kholilah, Kholilah; Kohar, Zawawi; Fitantina, Fitantina; Zapri, Zapri (Universitas Muhammadiyah Palembang, 2019)
ABSTRACT Purpose - The purpose of this study was to determine the effect of leadership, organizational climate and employee motivation on the performance of PT. Perkebunan Nusantara VII (PTPN VII) Betung.Design/methodology - Primary data is needed as the basis of analysis, while the data collection technique is a questionnaire. The analytical technique used is multiple linear regression. Simultaneous hypothesis test (F) and partial (t).Findings - The results of multiple linear regression analysis show that there is a positive influence of leadership, organizational climate and work motivation and significant effect on the performance of PTPN VII Betung. The results of partial analysis show that there is a positive influence of leadership, organizational climate and work motivation have a positive and significant effect on the performance of PTPN VII Betung.